Significance of fault-current-limiters and parameters optimization in HVDC circuit breakers for increased capacity of VSC-HVDC transmission networks application. (November 2022) - Ahmad, Muhammad; Wang, Zhixin; Shafique, Muhammad; Nadeem, Muhammad Haroon
Abstract: The voltage and current ratings of the voltage source converter (VSC) based high voltage direct current (HVDC) transmission line projects have increased over the years. It testifies the increasing popularity of VSC-HVDC technology. Since the long-distance, VSC-HVDC transmission lines are more exposed to commonly appearing short circuit faults; thus, protection equipment with increased fault-current handling capability is required. The DC circuit breakers (DCCBs), with or without fault current limiters (FCLs), can effectively handle the fault-current. The variations in VSC-HVDC projects' ratings and their impact for DCCB with FCL and without FCL are thoroughly analysed in this paper. The paper further includes an in-depth discussion on DCCBs with FCL and without FCL. An equivalent circuit modelling approach is used for simulation analysis of three case studies under the influence of these breakers to analyse current behaviour; the case studies include the Zhoushan HVDC Project, Xiamen HVDC Project, and Zhangbei-I HVDC Project. All these projects have different capacities in terms of their power, voltage, and current ratings. For DCCBs, this paper includes a detailed analytical model to understand the fluctuations in the size of fault-current limiting components (in DCCBs) for increased fault-current handling requirements. The simulation results using PSCAD/EMTDC and MATLAB are presented to verify different aspects of this study. A small scale laboratory prototype is also developed to validate the performance of DCCB with and without FCL. Based on theoretical, simulation, and experimental validations, it is substantiated that for increased VSC-HVDC projects' ratings, DCCB with FCL can perform better compared to conventional DCCB without FCL.